HTML5 & CSS3 for dummies - Karlins, David (Hoboken, N.J. : John Wiley & Sons, 2014)
Learn to create powerful and unique websites with HTML5 and CSS3 HTML5 and CSS3 have ushered in an entirely new era in web development and web design. This easy-to-understand full-color guide presents the elements of design and development as equal; therefore, both designers and developers will benefit from learning how to leverage the power behind HTML5 and CSS3. The two-page spreads and helpful insight show you how to use HTML5 and CSS3 in conjunction in order to create websites that possess both powerful function and beautiful design. Incorporates all the trademark elements of the For Dumm
Includes index.
Keywords: HTML (Document markup language); Cascading style sheets